«aber wir waren uns einig, daß neue Ideen am deutlichsten in der Briefform dargestellt werden können». Über Hölderlins Briefe (Studia theodisca, 2017)
Hölderlins letters form an integral part of his work. Their proper mode of diction and specific dignity gets clear especially within the contemporary resp. sociocultural context of the epoch-threshold 1800. The contribution outlines this context: the civil achievement of a communicative culture at the crossroads of privacy and publicity. Within this framework exemplary elucidated are letters Hölderlin wrote to Hegel, Niethammer, Ebel and Böhlendorff. Special attention is finally directed on the discussion with Schiller’s concept of “aesthetic education”.